Firm and industry effects on small, medium-sized and large firms' performance - Esteban Fernández Sánchez; Susana Iglesias-Antelo; Vicente López-López; Marcos Rodríguez-Rey; Carlos M. Fernandez-Jardon (BRQ Business Research Quarterly, 2019)
This paper examines whether or not the relative importance of the firm and industry effects in explaining performance variations is the same regardless of the firm size. In relation to size, we think that there has been particular neglect of studying medium-sized firms separately from SMEs in general. That is why we study separately large, medium-sized and small firms. We also contribute to knowledge on the firm-industry debate testing empirically both effects distinguishing the firms by size according to a standard classification in the EU. Our results show that the performances of large and small firms are mainly explained by the firm effect, albeit for different reasons, while the performance of medium-sized firms is explained primarily by the industry effect.
Keywords: L11; L25; M21; 650; Firm effect; Firm size; Industry effect; Organizational performance; SMEs